2010
DOI: 10.3109/02841851.2010.520027
|View full text |Cite
|
Sign up to set email alerts
|

CT, MR, 18F-FDG PET/CT, and their combined use for the assessment of mandibular invasion by squamous cell carcinomas of the oral cavity

Abstract: the combined analysis of CT, MR, and PET/CT can improve sensitivity in the detection of mandibular invasion by SCC of the oral cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 24 publications
(1 reference statement)
3
40
0
7
Order By: Relevance
“…The comparison studies showed that the sensitivity and specificity rates are 87%-90% and 80%-93% for FDG-PET, and 61%-97% and 21%-100% for CT-MRI [4] . In literature there are many propective and retrospective studies comparing PET or PET/CT with CI at both initial staging and restaging [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . CI modalities are still the methods of choice for the evaluation of primary tumor in head and neck cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison studies showed that the sensitivity and specificity rates are 87%-90% and 80%-93% for FDG-PET, and 61%-97% and 21%-100% for CT-MRI [4] . In literature there are many propective and retrospective studies comparing PET or PET/CT with CI at both initial staging and restaging [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . CI modalities are still the methods of choice for the evaluation of primary tumor in head and neck cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…27 The same study is suggested for PET/ CT and MRI. 29 Thus, to consider erosion as an invasion criterion requires that an agreement be established on the minimum slice thickness for detection of mandibular bone tissue invasion by SCC. Likewise, every report should be more explicit with respect to the classification scale used such that values will be considered positive (bone tissue invasion) and negative (no bone tissue invasion) for later comparison against the reference standard.…”
Section: Discussionmentioning
confidence: 99%
“…For CT, differences in slice thicknesses of between 1.5 mm and 6 mm were observed 27,30 as well as in amperage, with values of between 100 and 200 mAs. 29,30 Slice thickness for MRI also varied, from 3 to 6 mm. 28,29 Receiver operating characteristic (ROC) curves were not prepared because the different scales and criteria used did not permit generation/ definition of cutoff points for the different studies.…”
Section: Heterogeneity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…15 Gu et al 16 performed a direct comparison of CT and MRI and PET/CT in the detection of mandibular invasion by OCC. The sensitivity was 47.1%, 58.3% and 58.3% for CT, MRI and PET/ CT, respectively.…”
Section: Mandibular Invasionmentioning
confidence: 99%